DETERMINANTS OF SHARE PRICE IN MANUFACTURING COMPANIES LISTED ON THE IDX IN 2020-2022 - Jenny Zain; Stefany Graciela; Irna Triannur Lubis (SEAN Institute, 2023)
The share price reflects the value of a company. Valuation of stock prices is very important for investors before investing because stocks are a type of investment that is profitable for investors. Stock prices always increase or decrease. The better the company's financial performance, the more the shares will be enjoyed and the share price will increase. Therefore, several possible variables of this study were conducted to find out whether there is an influence between Return On Assets, Debt to Equity Ratio, Return On Equity, and Earning per Share on the Determinants of Stock Prices. The population in this study is 360 Manufacturing Companies for the 2020-2022 period. The sampling method used to make this journal is purposive sampling. Based on the results of the research conducted, shows that Return On Assets, Return On Equity, and Earning per Share have a positive effect on the determinants of stock prices. Meanwhile, the Debt to Equity Ratio does not show a significant effect on the Determinant of Stock Prices